PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP PERILAKU EKSISTENSI MAHASISWA : Studi Deskriptif terhadap Mahasiswa FPIPS UPI - Agni Fauzullah Rachmat, - (2019)
As time went Instagram became increasingly a means to show the existence of an individual. Even in the midst of its popularity Instagram is often a news media and even a visualization of themselves to the public audience. However, Instagram has no restrictions on it's users to exist in the accounts they have. This research uses a quantitative approach with descriptive study methods. Data collection was carried out using a questionnaire technique with answer choices using the Likert scale technique. Assisted with observation, documentation, and literacy study techniques. The results of this study indicate that 1). FPIPS UPI students not always use Instagram to conduct existence behavior when uploading photos or videos on Instagram. 2). the majority of instagram users are women who first got to know Instagram from the age of 14 to 18 years. 3). The use of Instagram on the existence behavior of UPI FPIPS students falls into the category of normal limits and does not change their existence. Keywords: Instagram, Existence Behavior